2008
DOI: 10.3340/jkns.2008.43.5.221
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Experience of the Dynamic Stabilization System for the Degenerative Spine Disease

Abstract: The results of this study show that the Dynesys system could preserve the motion of stabilized segments and provide clinical improvement in patients with degenerative spinal stenosis with instability. Thus, dynamic stabilization systems with adequate decompression may be an alternative surgical option to conventional fusion in selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
46
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 17 publications
2
46
0
2
Order By: Relevance
“…23 The efficacy of the Dynesys system as a posterior lumbar dynamic stabilization device has been supported by published biomechanical as well as clinical studies. 6,10,12,19 In their anatomical study, Strube et al concluded that increasing the fused levels and stiffness of a fusion system would result in compensatory increase of the range of mobility of the adjacent segment, which might lead to or accelerate the degenerative process in the adjacent segment. They also found that using the Dynesys system adjacent to a singlelevel fusion might prevent hypermobility in the adjacent level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 The efficacy of the Dynesys system as a posterior lumbar dynamic stabilization device has been supported by published biomechanical as well as clinical studies. 6,10,12,19 In their anatomical study, Strube et al concluded that increasing the fused levels and stiffness of a fusion system would result in compensatory increase of the range of mobility of the adjacent segment, which might lead to or accelerate the degenerative process in the adjacent segment. They also found that using the Dynesys system adjacent to a singlelevel fusion might prevent hypermobility in the adjacent level.…”
Section: Discussionmentioning
confidence: 99%
“…22 In an attempt to address the problem of adjacent-level disease and degeneration, posterior dynamic stabilization devices have been developed. 2,12,13,15,[19][20][21] Posterior dynamic stabilization, in which pedicle screw fixation is coupled with a flexible longitudinal connecting system, presumably allows for the normalization of intersegmental motion. This stands in contrast to traditional fusion surgery, in which the goal is complete and immediate elimination of motion and, ultimately, arthrodesis.…”
Section: Discussionmentioning
confidence: 99%
“…34,40,41,51,59 Recently, a nonfusion stabilization system with motion preservation (Dynesys system, Zimmer Spine) has been explored as an alternative to fusion in an effort to reduce adjacentsegment disease (ASD) and maintain greater physiological movement and function. 31,32,47,61 Dynesys is a pedicle screw-based dynamic stabilization system that has been used since 1994 and consists of pedicle screws, flexible spacers, and cords. 26,41 This assembly attempts to neutralize the abnormal forces after surgical intervention at the lumbar spine and maintain a more favorable biomechanical environment for segmental motion.…”
mentioning
confidence: 99%
“…21 Some clinical studies have found positive outcomes with improved Oswestry Disability Index (ODI) and visual analog scale (VAS) pain scores, as well as shorter recovery times, for patients with degenerative lumbar disease treated using the Dynesys system compared with those of patients who underwent fusion. 18,25,27,33,38,39 Although the early outcomes have been promising, the long-term effects are still debated.…”
mentioning
confidence: 99%
“…30 Fusion surgery has been associated with several undesirable effects, such as pseudarthrosis, nonunion, instrumentation failure, and adjacent-segment degeneration (ASD). 18 Even if solid fusion occurs, persistent back pain sometimes haunts surgeons and patients. 30 The Dynesys system (Zimmer, Inc.), a semirigid pediclebased dynamic stabilization (PDS) system, was introduced in an attempt to overcome the drawbacks of fusion procedures.…”
mentioning
confidence: 99%